Tuberculosis in a Health District of Ecuador: epidemiological situation and control of the disease. Years 2017 and 2018. - Pereira Olmos, Hugo (2021)
Introduction: Tuberculosis is the ninth cause of death in the world and the first of infectious diseases. The objective of this study was to describe the epidemiological situation of tuberculosis and the scope of the response of the control strategy in a health district in the highlands of Ecuador. Materials and methods: descriptive study, with secondary information from the database of records of people with tuberculosis of the Health District 17D06 Chilibulo - Lloa; personal identification data was kept strictly anonymous and confidential. Results: In 2017 and 2018 there were 39 and 44 cases of tuberculosis; 61% were male; 71.8% were older than 35 years; the mortality rate was 0.02 and 0.97 per 100,000 inhabitants. The uptake was 15.5% in 2017 and 17.9% in 2018. The gaps in uptake of respiratory symptoms, diagnosis of tuberculosis with positive smear microscopy and its total were above 80% in both years. Of the patients who started treatment, 87.2% finished it in 2017 and 31.8% in 2018. Discussion: The treatment success rate in 2017 is like the goal set at the national level (87%), somewhat lower than in 2018. The achievements in recruitment also differ from the rest of the country (30%), Conclusion: The health district carries out adequate monitoring in the treatment of people with tuberculosis but fails to capture patients with respiratory symptoms.